Epistemological Tensions in Bourdieu’s Conception of Social Science - Susen, Simon (Teorie vědy / Theory of Science, 2011)
This paper explores Pierre Bourdieu’s conception of social science. In particular, it aims to show that the common assumption that Bourdieu remains trapped in a positivist paradigm does not do justice to his multifaceted account of social science. In order to illustrate the complexity of Bourdieu’s conception of social science, this study scrutinises ten epistemological tensions which can be found in his writings on the nature of systematic forms of knowledge production. In view of these epistemological tensions, a more fine-grained picture emerges which demonstrates that Bourdieu compels us to reflect upon the complexity of the various tasks intrinsic to the pursuit of a critical social science. The paper concludes by discussing the limitations and shortcomings of the epistemological presuppositions that underpin Bourdieu’s reflexive sociology.